EDUCATION TRANSFORMATION IN THE DIGITALIZATION AGE AS THE FUTURE OF THE NATION - Edward Sitepu; Milisi Sembiring; A Dan Kia; Sostenis Nggebu (English Lecturers and Teachers Association (ELTA), 2022)
Technology-based education is expected to be able to improve the quality of education and also in the long term improve the welfare of a nation. The case study approach in several countries and using the results of existing studies in those countries shows a significant influence on digital technology-based learning and teaching. This was emphasized by UNDP regarding the importance of using technology in learning. Studies in England, Turkey and in Asean countries and specifically in Indonesia show that improving the welfare of the nation is possible because more advanced education and the use of learning technology are able to shape students' thinking, learning attitudes and of course their independence in the future. This is certainly encouraging in the midst of the Government's spirit to promote education with an independent learning corps as a complementary to education for all. Keywords: education, technology, welfare, nation, learning and teaching.